(untitled) (Applied Biological Research, 2024)
Datura metel, a well-known medicinal herb, exhibits poisonous and therapeutic attributes, showcasing its significant pharmacological potential. The present study focused on phytochemical screening of D. metel through TLC and LC-MS, antimicrobial assay and in-vitro callus inuction of D. metel through leaf and stem explants. The bioactive compounds from leaf and stem were extracted in ethyl acetate, methanol, and distilled water. Antibacterial activity of D. metel against pathogenic bacteria Escherichia coli and Staphylococcus aureus was performed. The leaf and stem explants were cultured on MS medium supplemented with 30 g L-1 sucrose, 8 g L-1 agar, and varying combinations of 2,4-D, BAP, kinetin, IAA, and NAA to explore their effects on callus induction. LC-MS analysis of D. metel confirmed the presence of three alkaloids viz., choline, atropine, and ambelline in its extract. Antimicrobial assay revealed maximum zone of inhibition in ethyl acetate leaf extract (10 mm), with methanolic and aqueous leaf extracts showing minimum zone of inhibition (9 and 8 mm) against S. aureus. The MS basal medium supplemented with 2, 4-D + kinetin + IAA (1.5:2:1 mg L-1) combination resulted in early callus initiation on 15th day after inoculation.